In Silico Identification of Promising PDE5 Inhibitors Against Hepatocellular Carcinoma Among Natural Derivatives: A Study Involving Docking and ADMET Analysis - Kumar, Anil; Rajput, Dharmendra; Gupta, Naveen; Singh, Harpreet; Chopra, Shivani; Chopra, Hitesh (Drug Research, 2024)
Hepatocellular carcinoma (HCC) represents a significant worldwide health challenge due to its high mortality rate, underscoring the need for advanced therapeutic strategies. This study employs a computer-based method to identify potential phosphodiesterase 5 (PDE5) inhibitors from a library of approved IBS_Scaff 532 natural compounds. PDE5 inhibitors have gained attention for their potential anti-tumor effects. Using molecular docking simulations, the researchers assessed how well these compounds bind to the PDE5 enzyme, which regulates cellular cGMP pathways. Additionally, ADMET profiling predicted the pharmacological and safety properties of candidate inhibitors. Notably, compounds like IBS_NC-0322 and IBS_NC-0320 exhibited favorable ADMET properties and strong binding affinities. These findings suggest their potential as therapeutic agents for treating HCC. While in silico methods serve as valuable screening tools, subsequent experimental validation and clinical trials are essential for confirmation.
Keywords: ADMET; cGMP; hepatocellular carcinoma (HCC); molecular docking; phosphodiesterase 5